Wujudkan Keluarga Sehat dan Bahagia Melalui Pencegahan Penyakit Tidak Menular dengan Perilaku “CERDIK” - Sarah Geltri Harahap; Ellynia Ellynia; Paramita Boni; Fariz Kahendra (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Non-Communicable Diseases (NCDs) remain a health issue that remains unresolved. Health education based on healthy lifestyle behaviors can be a preventative measure, specifically through the CERDIK approach. The purpose of this study was to determine the effect of CERDIK health education on respondents' knowledge levels. The study was conducted by administering pre-tests and post-tests before and after the education, involving 30 respondents. The instrument used was a questionnaire with 20 questions, and the results of each respondent's answers were then tested univariately to see the picture of knowledge and bivariate to see the resulting effect. The results of the univariate analysis showed that after the education was given, 30% had high knowledge, 66.7% had moderate knowledge, and 3% had low knowledge. In the bivariate comparison using the t-dependent test, the results also showed a significant effect (p-value = <0.001) between CERDIK education and increasing respondents' knowledge regarding NCD prevention, as evidenced by an increase in the average score from 45.50 to 70.50. In this way, after health education is carried out, it is hoped that the community will be able to implement steps to prevent NCDs in their daily lives so that NCD problems can be resolved.